Dynamic expression of transformating growth factor-β1 and caveolin-1 in the lung of Bleomycin-induced interstitial lung disease - Xing, Yida; Wang, Li; Wang, Hongjiang; Kong, Xiaodan; Zhan, Libin (Journal of Thoracic Disease, 2017)
Background: Interstitial lung disease (ILD) is a disease with high mortality worldwide. Unfortunately, its prognosis is still very poor. Therefore, developing the target molecular is very important for ILD diagnosis and treatment. Caveolin-1 (Cav-1) can regulate the formation of fibrosis by linking to the signaling pathway of transforming growth factor-β1 (TGF-β1), which is generally considered to be the most effective approach to solve the problem of ILD. Methods: The rat model of ILD was induced by disposable transtracheal injection of bleomycin hydrochloride. Rats were sacrificed in batches on days 7, 14, 21 and 28 after modeling, and the lung tissues was obtained for histopathological examination (HE) and Masson staining. Expressions of TGF-β1 and Cav-1 in the lungs were measured by western blot and real-time polymerase chain reaction (RT-PCR). Results: Pulmonary inflammation was observed in lung tissue from day 7 after modeling; fibrosis was observed from day 14 after modeling; the collagen deposition reached the peak on day 21. Significant TGF-β1 up-regulation and Cav-1 down-regulation appeared in the inflammatory phase (7d); TGF-β1 expression level reached the peak and Cav-1 expression level reached the minimum on day 21–28 with the most obvious fibrosis. Conclusions: The rat model of bleomycin induced pulmonary fibrosis can be used to dynamically observe the progress of ILD. In the lung tissues from inflammation to fibrosis, TGF-β1 expression was significantly up-regulated and Cav-1 expression was significantly down-regulated. The regulation of two protein expressions is closely related to the occurrence and development of ILD in rats. The regulation of TGF-β1 and Cav-1 expressions and the balance between the two can be used as a possible target of ILD therapeutic intervention.